Cathedral bell's San José de Cúcuta: Heritage and acoustics (2019)
The objective of this research was to analyze the characteristics of the bells and dynamic particularities of the bell tower of the cathedral of San José de Cúcuta, Norte de Santander, Colombia. The research had a mixed methodological approach, using a simplified numerical model of the structure. The spectrum of structural response is determined, analyzing according to the bells, magnitudes of the function of variable forces, with the time that they introduce on the structure with their own weight, speed of rotation and inertia; the most unfavorable dynamic amplification factor and response for quasi-static analysis for forces is determined. It is concluded that the bell of greater weight introduces greater efforts in the tower, being the location of the bell a direct incident factor.